Analisis Deiksis Semantik Dalam Cerpen Bawang Putih Bawang Merah - Siagian, Irwan; Shofyan, Muhammad Shofiyudin; Abadi, Muhammad Adilah; Lutfiyanti, Nur Anisa; Prayono, Novi Monicka; Mufidah, Ana; Stevany, Marlina; Nurhadijah, Nabila (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aims of this research are: (1) To describe the types of persona deixis found in the short story collection "Bawang Putih and Bawang Merah". This study used descriptive qualitative method. Qualitative methods are procedures that produce descriptive data in the form of written or spoken data in language communities (Sugiyono, 2012). In other words, the amount of data is determined according to research needs. Based on the analysis carried out, this research obtained the following results: (1) the forms of personal deixis found were the first, second and third forms of personal deixis. Each form of deixis consists of a singular form and a plural form. (2) the form of personal deixis with the highest frequency of appearance.